Optimization of Aptamer-Based Electrochemical Biosensor for ATP Detection Using Screen-Printed Carbon Electrode/Gold Nanoparticles (SPCE/AuNP) - Rahmaniar Mulyani; Nida Yumna; Iman Permana Maksum; Toto Subroto; Yeni Wahyuni Hartati (Indonesian Journal of Chemistry, 2022)
Electrochemical biosensors are used to detect adenosine triphosphate (ATP) levels, which are involved in a variety of biological processes, such as regulating cellular metabolism and biochemical pathways. Therefore, this research aims to develop an aptamer-based electrochemical biosensor with Screen Printed Carbon Electrode/gold nanoparticles (SPCE/AuNP) and collect data as well as information related to ATP detection. The modification of SPCE with AuNP increased the analyte’s binding sensitivity and biocompatibility. The aptamer was selected based on its excellent bioreceptor characteristics. Furthermore, aptamer–SH (F1) and aptamer-NH2 (F2) were immobilized on the SPCE/AuNP surface, which had been characterized using SEM, EIS, and DPV. Also, the ATP-binding aptamers were electrochemically characterized using the K3[Fe(CN)6] redox system and Differential Pulse Voltammetry (DPV). According to the optimization results using the Box-Behnken experimental design, the ideal conditions obtained from the factors influencing the experiment were the F1 concentration and incubation time of 4 µM and 24 h, respectively, as well as F1/F2/ATP incubation time of 7.5 min. Meanwhile, for the range of 0.1 to 100 µM, the detection (LoD) and quantification (LoQ) limits were 7.43 and 24.78 µM, respectively. Therefore, this aptasensor method can be used to measure ATP levels in real samples.